Consumer Perception and Acceptance of Pasteurised Pineapple Juice With Encapsulated Probiotics - Siti-Mariam, A Rani; Kasim, Khairul Farihan; Lee, Boon-Beng; Elias, Nor Hidawati; Ahmad, Nor’izah; Ya’kub, Mohd Khairul; Sofian-Seng, Noor-Soffalina (Malaysian Applied Biology, 2026)
Fresh pineapple juice is widely appreciated for its numerous health benefits derived from the nutrients in the fruit. Current busy lifestyles have caused many people to prefer ready-to-drink commercial functional juices, such as probiotic-added juice. The probiotics are encapsulated to preserve their bioavailability and survivability in the acidic juice. However, consumer acceptance of this enhanced juice remains uncertain, as the heating process and the addition of encapsulated probiotics may change the juice’s sensory parameters (taste, texture, and colour). Therefore, focus group discussion (FGD) sessions (n=18) were conducted to assess consumer perception and acceptance of pasteurised pineapple juice with encapsulated probiotics. The FGD sessions assessed general fruit consumption, safety concerns, and health benefits of taking probiotics. The findings revealed that 100% consumers preferred the safety provided by pasteurisation and the additional health benefits associated with the addition of encapsulated probiotics to the juice. The acceptance of this experimental juice formulation indicates its potential for commercial applications.